Clinical Predictors of Meningitis Among Children with Febrile Illness - Dr. Taiba Abbas, Dr. Aafia Khalid, Dr. Maqsood Ahmad, Dr. Sughra Wahid, Dr. Anam Zafar, Dr. Sarmad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Meningitis remains a critical cause of morbidity and mortality among children, and early recognition is challenging because its initial symptoms often overlap with common febrile illnesses. Objective: To evaluate the clinical features associated with meningitis and identify independent predictors among children presenting with febrile illness. Methods: This descriptive cross-sectional study was conducted at Department of Pediastrics, KRL Hospital, Islamabad from January 2023 to June 2023. It included 135 children aged one month to 15 years presenting with fever and suspected central nervous system involvement. Demographic characteristics, clinical features, neurological signs, and laboratory findings were recorded using a structured proforma. Meningitis was confirmed based on cerebrospinal fluid analysis and clinical assessment. Results: Meningitis was confirmed in 38 children (28.1 percent). Several clinical features were significantly more common in meningitis cases, including seizures (55.3 percent vs. 20.6 percent, p < 0.001), vomiting (71.0 percent vs. 46.4 percent, p = 0.008), irritability (65.8 percent vs. 33.0 percent, p = 0.002), altered consciousness (47.4 percent vs. 11.3 percent, p < 0.001), neck stiffness (42.1 percent vs. 6.2 percent, p < 0.001), photophobia (26.3 percent vs. 5.2 percent, p = 0.001), and focal neurological deficits (21.1 percent vs. 4.1 percent, p = 0.003). Bulging fontanelle was observed exclusively in infants with meningitis. Logistic regression identified altered mental status (AOR 5.10), neck stiffness (AOR 4.70), seizures (AOR 3.90), vomiting (AOR 2.80), bulging fontanelle (AOR 3.65), and focal deficits (AOR 2.92) as independent predictors. Conclusion: Several clinical features, particularly neurological signs, serve as strong predictors of meningitis in febrile children. Integrating these predictors into routine clinical assessment may improve early recognition and reduce diagnostic delays, especially in resource-limited settings. Keywords: meningitis, children, fever, clinical predictors, neurological signs, cerebrospinal fluid.